The Intellectual Foundations of Putinism: A Critical Study (قضايا سياسية, 2025)
Putinism is a controversial political phenomenon associated with President Vladimir Putin. Given the turbulent changes the country experienced after the fall of communism, it was not easy for those who assumed power to establish intellectual or ideological frameworks to fill the void left by communism, which had dominated thought and politics for more than eight decades.Former Russian President Boris Yeltsin was preoccupied with managing the transition from a totalitarian regime to a liberal democratic system open to the West, making Russia part of the Western world. The post-communist era was not easy for Yeltsin; rather, it was a very difficult phase of reconstruction from the ruins of an entire empire.